Exploring learners’ understanding of technical vocabulary in Traditional Chinese Medicine - Lu, Cailing; Boers, Frank; Coxhead, Averil (Studies in Second Language Learning and Teaching, 2021)
This study explores English for specific purposes learners’ understanding of technical words in a previously-developed technical word list in Traditional Chinese Medicine (TCM). The principal aim was to estimate what kind of technical terms pose problems to TCM learners and might therefore merit special attention in instruction. Of particular interest was the question whether there is a divergence in the understanding of technical vocabulary in TCM between Chinese and Western background learners. To achieve these aims, a combination of word association tasks and retrospective interviews was implemented with 11 Chinese and 10 Western background TCM learners. The data showed that both Chinese and Western learners encountered certain difficulties in understanding technical vocabulary in their study. However, their sources of difficulty were different. Comparisons of typical word associations between Chinese and Western learners indicated that there was a degree of divergence in the way these two participant groups understood TCM terms.